ACCOUNTING AND ANALYTICAL SUPPORT FOR ECONOMIC SECURITY OF ENTERPRISE - Hnatiuk , T. M.; Melnyk , N. B.; Banashkevych , T. P. (The actual problems of regional economy development, 2016)
The importance of economic security of the enterprise in its functioning is studied. The essence of the accounting and analytical support is defined. An accounting and analytical support of economic security of the entity is determined. Their importance is revealed and the necessity of the formation of each of the components of economic security (financial, political, legal, intellectual, human resources, technology, information, environmental, social, power components) is grounded. JEL: M41